Effects of different irrigation methods on pepper yield and soilborne diseases incidence - Seral YÜCEL; Hale GÜNAÇTI; S. Metin SEZEN (Derim, 2013)
In this study, the effect of different irrigation strategies and irrigation methods on yields and the incidence of wilt (Fusarium oxysporum) and root rot (Fusarium solani and Macrophomina phaseolina) diseases causing significant yield losses on field grown processing red pepper is determined. Experiments were carried out at Topçu Station of the Soil and Water Resources Research Institute of Tarsus in 2010 and 2011. Karaisalı processing pepper (Capsicum annuum L.) was used in the experiments. Three furrows and five drip irrigation treatments were used in the study. The disease incidence rates were found 8.0-18.2% in furrow irrigation plots and 4.5-10.0% in drip irrigation plots in 2010, while it was 3.4-9.7% in furrow irrigation plots and 2.2-4.5% in drip irrigation plots in 2011. Pepper yields ranged from 3 416 to 4 417 kg da-1 and 3 376 to 4 779 kg da-1 in drip irrigated plots in 2010 and 2011, respectively. However, yields varied between 3 172-3 559 kg da-1 and 2 932-4 150 kg da-1 in furrow irrigated plots in 2010 and 2011 growing seasons.